2008
DOI: 10.1038/ijo.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

The increase of fatty acid-binding protein aP2 in overweight and obese children: interactions with dietary fat and impact on measures of subclinical inflammation

Abstract: Background:In adults, circulating aP2 may link obesity, inflammation and the metabolic syndrome, but there are few data in children. Experimental models support that dietary factors, particularly dietary fat, may be major determinants of phenotype. Objective: The aim of this study was to investigate, in normal, overweight and obese children, the relationships among aP2, the metabolic syndrome, inflammation and diet. Design: This was a cross-sectional study conducted in Northern Switzerland. Subjects: Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
3
13
0
1
Order By: Relevance
“…Studies in children have shown that excessive intake of high-fat diets increases the risk for overweight and obesity [2,3]. Increased fat intake in pre-adolescent children has been associated with subclinical inflammation, dyslipidemia, systemic insulin resistance and elevated blood pressure [4,5]. Obesity in children is also the major risk factor for development of pediatric non-alcoholic fatty liver disease (pNAFLD), defined histologically as ≥5% of hepatocytes containing macrovesicular lipid droplets [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in children have shown that excessive intake of high-fat diets increases the risk for overweight and obesity [2,3]. Increased fat intake in pre-adolescent children has been associated with subclinical inflammation, dyslipidemia, systemic insulin resistance and elevated blood pressure [4,5]. Obesity in children is also the major risk factor for development of pediatric non-alcoholic fatty liver disease (pNAFLD), defined histologically as ≥5% of hepatocytes containing macrovesicular lipid droplets [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Data on relationships between diet and metabolic factors from a subgroup of these children (n ¼ 79) have been published previously. [18][19][20][21] Informed written consent was obtained from the parents and informed oral assent from the children. Ethical approval for the study was obtained from the ethics committee of the Swiss Federal Institute of Technology in Zürich.…”
Section: Methodsmentioning
confidence: 99%
“…Some case-control studies have shown that FABP4 is elevated in obese children compared with normal weight children [10][11][12][13][14], whereas one case-control study did not find any differences [15]. We are aware of only two studies in unselected children that have attempted to investigate relationships between FABP4 and different measures of body fat [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 has also been investigated in young subjects. A few case-control studies have shown that FABP4 is elevated in obese children compared with normal weight children [10][11][12][13][14], but this is not the case in all studies [15]. Weight loss [10,12] and nutritional counseling and supplementation with encapsulated fruit and vegetable juice concentrate have been shown to decrease FABP4 levels [14].…”
Section: Introductionmentioning
confidence: 99%